PENDEKATAN PEMBELAJARAN BAHASA INGGRIS BERBASIS ISLAM DALAM MENINGKATKAN SIKAP MODERASI BERAGAMA DI SMK MADINATUL ULUM JEMBER - Herlinda Herlinda; Mahnawawe Yakoh (Program Studi Pendidikan Agama Islam, 2024)
This study aims to explore the Islamic-based English language learning approach in enhancing religious moderation attitudes at SMK Madinatul Ulum Jember. Considering Indonesia as the country with the largest Muslim population in the world, education plays a strategic role in shaping students' character and attitudes. This approach emphasizes the importance of Islamic values such as tolerance, openness, and ethics, which support multicultural education and religious moderation. The findings suggest that by integrating these values into English language learning, students can develop a moderate attitude that avoids extremism and intolerance, thereby contributing to the creation of a harmonious and tolerant society.